The Relationship between Job Stress, Job Satisfaction and Career Development with Turnover Intention Among Production Workers in X Bakery Company - Low , Xing Yi; Atan, Siti Anisah (Research in Management of Technology and Business, 2025)
This study examines the factors that impact employee turnover intentions at X bakery company, emphasizing job stress, job satisfaction, and career development possibilities. The research objectives are to determine the employee turnover intention level among production employees at X bakery company and to investigate the relationship between job stress, job satisfaction, career development, and employee turnover intentions among production employees at X bakery company. The findings show that excessive job demands, insufficient resources, and a lack of professional growth chances are significant factors in employee discontent and stress, which drive turnover. The researcher will better grasp the subject by using quantitative methods and SPSS analysis to collect data and then doing descriptive and correlational analysis assessments. The research will gain valuable insight to X bakery company management to design employee retention strategies to retain the employees